2021
DOI: 10.1038/s41598-021-96839-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of delirium on the intensive care unit in patients with acute kidney injury, insight from a retrospective registry

Abstract: Acute kidney injury (AKI) and delirium are common complications on the intensive care unit (ICU). Few is known about the association of AKI and delirium, as well as about incidence and predictors of delirium in patients with AKI. In this retrospective study, all patients with AKI, as defined by the KDIGO (kidney disease improving global outcome) guideline, treated for more than 24 h on the ICU in an university hospital in 2019 were included and analyzed. Delirium was defined by a NuDesc (Nursing Delirium scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Specifically, a 1.5-fold increased risk of delirium was observed with KDIGO stage 2 (OR 1.55; 95% CI, 1.07–2.26) and a 2.5-fold increased risk of delirium with stage 3 (OR 2.56; 95% CI, 1.57–4.16) AKI, while KDIGO stage 1 was not significantly associated with delirium (OR 1.13, 95% CI 0.91–1.41) [ 2 ]. Concordant data were reported in a retrospective study that analyzed the medical records of 919 medical ICU patients of whom 41.6% developed AKI and found a higher incidence of delirium with KDIGO stage 2 (66.7%) and stage 3 (66.9%) AKI compared with KDIGO stage 1 (53.6%) [ 1 ]. Another prospective cohort study of 304 patients aged 60 or older found elevated creatinine level of > 2 mg/dL (OR 2.1, 95% CI 1.1–4.0) as one of 4 admission risk factors for delirium along with dementia, receipt of benzodiazepines before ICU admissions, and low arterial pH [ 24 ].…”
Section: Background and Epidemiologymentioning
confidence: 60%
See 2 more Smart Citations
“…Specifically, a 1.5-fold increased risk of delirium was observed with KDIGO stage 2 (OR 1.55; 95% CI, 1.07–2.26) and a 2.5-fold increased risk of delirium with stage 3 (OR 2.56; 95% CI, 1.57–4.16) AKI, while KDIGO stage 1 was not significantly associated with delirium (OR 1.13, 95% CI 0.91–1.41) [ 2 ]. Concordant data were reported in a retrospective study that analyzed the medical records of 919 medical ICU patients of whom 41.6% developed AKI and found a higher incidence of delirium with KDIGO stage 2 (66.7%) and stage 3 (66.9%) AKI compared with KDIGO stage 1 (53.6%) [ 1 ]. Another prospective cohort study of 304 patients aged 60 or older found elevated creatinine level of > 2 mg/dL (OR 2.1, 95% CI 1.1–4.0) as one of 4 admission risk factors for delirium along with dementia, receipt of benzodiazepines before ICU admissions, and low arterial pH [ 24 ].…”
Section: Background and Epidemiologymentioning
confidence: 60%
“…Delirium occurs in approximately 60% of patients with acute kidney injury (AKI) [ 1 ]. Substantial clinical evidence suggests a direct pathological role for AKI in delirium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictors that were found to be significantly related to the development of POD in our patient cohort included acute kidney injury (AKI). Previous studies [ 30 ] have indicated that higher AKI stages are a potential risk factor for POD development. Multiple pathophysiological mechanisms explain the enhanced delirium risk in patients with advanced AKI stages.…”
Section: Discussionmentioning
confidence: 99%